The development of open bite in patients with adenoid hypertrophy: clinical and radiological examination - M. E. Makarova; Z. S. Khabadze; Yu. A. Generalova; A. A. Kulikova; F. V. Badalov; M. Yu. Dashtieva; A. Yu. Umarov (Эндодонтия Today, 2024)
RELEVANCE. Adenoid hypertrophy, mouth breathing can significantly affect the development and formation of the dental system in children. One of the most difficult to correct malocclusion pathologies is anterior open bite. The literature contains isolated, sometimes contradictory reports on the effect of adenoid hypertrophy on the development of this type of malocclusion.AIM. To study the prevalence of adenoid hypertrophy in children aged 7 to 9 years with anterior open bite, paying special attention to the characteristics of the factors determining the development of this malocclusion.MATERIALS AND METHODS. 60 children aged 7 to 9 years with an orthodontic diagnosis of anterior open bite were included in the study. The patients were divided into two groups (comparative and control) based on otorhinolaryngological anamnesis (adenoid hypertrophy). According to the lateral cephalometry data, the tendency to skeletal anterior open bite was estimated. The correlation between the development of malocclusion and the presence of adenoid hypertrophy was assessed using the Pearson coefficient.RESULTS. This study included 30 children with anterior open bite and 30 without malocclusion. There was no strong correlation between the formation of an anterior open bite and the presence of hypertrophy of the pharyngeal tonsil. The skeletal growth type index according to the LC data did not differ significantly in both groups, but the average vertical ratio for children with adenoid hypertrophy and mouth breathing was significantly higher for the control group (p = 0.05).СONCLUSIONS. The presence of adenoid hypertrophy in a child is not one of the main factors in the open anterior bite development. However, it is necessary to consider that adenoid hypertrophy and mouth breathing, especially for a long time, increases the risk of malocclusion development, effects on the growth of maxillofacial structures, which justifies the need for consultations of pediatric patients with related specialists.